ОЦІНКА РОЗВИТКУ ОРГАНІЧНОЇ СИСТЕМИ ВЕДЕННЯ СІЛЬСЬКОГОСПОДАРСЬКОГО ВИРОБНИЦТВА В УКРАЇНІ (International Journal of Innovative Technologies in Economy, 2019)
Safety and quality of food is an important problem in many countries today, and environmental safety of agricultural products becomes one of the main factors of its competitiveness on domestic and foreign markets. Organic agriculture provides balanced state of the ecosystem that is the key to sustainable economic and social development of society. Development of the organic products market in Ukraine is essential for the formation of organic products supply on the European Union market. The purpose of the article is to determine the place of Ukraine in the formation of supply of the European market organic products. In the world, organic production began to emerge in the 20s of the twentieth century.Ukraine has significant natural and economic potential, which in perspective will become one of the most important subjects that will form the supply on this market. The purpose of the article is to determine the place of Ukraine in the formation of supply of the European market organic products.